IDEAS OF CLASSIFYING BIBLIOGRAPHY IN PRE-WAR LITHUANIA (HISTORICAL AND LOGICAL APPROACH) - ČEPYTĖ, JULIJA (Knygotyra, 2015)
The aim of the article has been to analyse the research object (the spread of the ideas of classifying bibliography in Lithuania of that period) on the basis of historical and logical aspects in context of book science and bibliography science, their quality, their scientific and practical value and place in the science of bibliography. The main focus of attention in Lithuania was maintened on bibliographical practice, not theory. That is why ideas of classification of bibliography were scarce, and were mainuly reflected in teaching aids of V. Ruzgas (1937) and V. Biržiška (1940–1941). Multi-aspects classification was popular (widely used) both in Lithuania and abroad. Out of wellknown available variants of socio-cultural classification activity in bibliography scholars used to chotose easten (Russian) direction, as the most interesting and mature approach. The article has explored V. Ruzgas’ multi-aspect classification of bibliography based on M. Schelkunov (1926) and that of V. Biržiška’s based on E. Schamurin (1933). In the Lithuania of that time there was a lack of the analysis and critical approach in the field of world bibliography classification ideas, but there existed a hidden reflection of the classification process, expressed by the original classification behaviours of Lithuanian book scientists and bibliographers. They either ignored some foreign ideas or uncritically reflected them in their works, or applied some of them for their needs with minor changes, mainly in the sphere of terminology. Kinds of bibliography that appeared in classifications, the terms used by Lithuanian authors were beneficial for specialists training, and forming of professional terminology and science of bibliography in Lithuania. Professional erudition of Lithuanian bibliographers enabled them to work on the level of achievements in bibliography science of that time.